Requalificação urbana e exclusão socioespacial : um estudo da área central “Beiral” de Boa Vista-RR - Walter, Pâmola Andreia Lemke (2021)
This research seeks to conduct a study about the removal of residents of “Beiral” from the urban requalification in the context of the reproduction of space in Boa Vista-RR. In this study, a brief analysis of basic concepts related to the processes for reusing consolidated urban spaces from the urban requalification processes is made. This theme is very current in the field of politics and urban planning, constituting as a strategy tool specifically directed to urban areas in decline, in this case the central area of Boa Vista. The investigation is focused on bibliographic and documentary research, fieldwork, data collection, elaborations of diagnosis and prognosis, guided by scientific practice from existing sources, as well as new sources to be explored in the field. The research also relies on Oral History, a methodology that consists in recording interviews with people who have experienced the “Beiral” problem. Through field research, we sought to verify the perception of the former residents of "Beiral" about the process of their removal and their new place of residence. The results identified that the 340 families removed from the “Beiral” received financial compensation with value lower than expected, and today they are in the most peripheral areas of Boa Vista. However, far from exhausting the possibilities of these discussions, this research is above all an invitation to renew efforts in order to continue the studies already carried out by myself and other researchers, to deepen them and to add new questions.